The boiling Peru of these days ... - Arguedas, José María (1981)
In José María Arguedas it is impossible to distinguish between the author of fictions and the social scientist, between the novelist and the anthropologist, because he used both imagination and analysis for the same purpose: to understand Andean men from their culture and mentality, to give testimony of a civilization that despite having persisted since the distant times of the conquest, was threatened by the overwhelming and leveling emergence of capitalism. These concerns moved the setting of his texts from the coastal mountains, specifically to the ports of Supe and Chimbote, where through the anchovy fishermen, recent migrants from the Andean peoples, he could follow the confrontation of a traditional culture faced with the capitalism and proletarianization.